2021
DOI: 10.1002/bab.2154
|View full text |Cite
|
Sign up to set email alerts
|

Under hypoxic conditions, MSCs affect the expression and methylation level of survival‐related genes in ALL independent of apoptosis pathways in vitro

Abstract: Mesenchymal stem cells (MSCs) are one of the most prominent cells in the bone marrow. MSCs can affect acute lymphocytic leukemia (ALL) cells under hypoxic conditions. With this aim, we used MOLT-4 cells as simulators of ALL cells cocultured with bone marrow mesenchymal stem cells (BMMSCs) under hypoxic conditions in vitro. Then, mRNA and protein expression of the MAT2A, PDK1, and HK2 genes were evaluated by real-time PCR and Western blot which was also followed by apoptosis measurement by a flow-cytometric met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…There was evidence that ADSCs play a key role in maintaining skin tissue structure, even as a physiological response to local damage, or as a mechanism for rejuvenation by seeding younger cells onto the outside of the epidermis ( Vishnubalaji et al, 2012 ; Marfia et al, 2015 ; Zhang et al, 2017 ). Studies have shown that MSCs play an important role in methylation involved in cell survival ( Marofi et al, 2022 ). Qiu et al reported that exosomes secreted by curcumin-treated MSCs reduced DNA methylation of miR-143 and miR-124 promoters and alleviated osteoarthritis ( Qiu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence that ADSCs play a key role in maintaining skin tissue structure, even as a physiological response to local damage, or as a mechanism for rejuvenation by seeding younger cells onto the outside of the epidermis ( Vishnubalaji et al, 2012 ; Marfia et al, 2015 ; Zhang et al, 2017 ). Studies have shown that MSCs play an important role in methylation involved in cell survival ( Marofi et al, 2022 ). Qiu et al reported that exosomes secreted by curcumin-treated MSCs reduced DNA methylation of miR-143 and miR-124 promoters and alleviated osteoarthritis ( Qiu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor 1 (HIF1) is an important transcription factor in response to hypoxic conditions containing two subunits including, an alpha subunit (HIF-1a, oxygen-sensitive subunit) and a beta subunit (HIF-1b). 170 , 171 It also has a role in cancer biologics such as tumor growth, metastasis, and angiogenesis. 172 Consistent with the previous studies, 173 , 174 He et al showed that hypoxia promoted cell cycle arrest and differentiation in myeloid leukemic cells.…”
Section: The Mir-17 and Mir-20a And Association With Stat3 And Hypoxi...mentioning
confidence: 99%